THE TRANSLATION OF INDONESIAN CONCEPTUAL METAPHORS FOUND IN THE NOVEL TARIAN BUMI INTO ENGLISH - Megantara I Gede (Universitas Pendidikan Ganesha, 2017)
The study concerned on the translation analysis of Indonesian conceptual metaphors found in the novel Tarian Bumi into English as found in its translation novel entitled Earth Dance. The objectives of this study were to identify and analyze the types of Indonesian conceptual metaphor and the translation strategies applied in translating them. The data were the sentences and quotations which belonged to Indonesian conceptual metaphors found in the Indonesian novel Tarian Bumi and their translation products that were found in the novel Earth Dance. This study applied the theoretical framework proposed by Lakoff and Johnson (1980) in identifying and analyzing the Indonesian conceptual metaphors. Meanwhile, in revealing the translation strategies used by the translator of the novel, the study applied the theoretical framework proposed by Larson (1998). Based on observation, this study revealed that Tarian Bumi consisted of 102 Indonesian conceptual metaphors in which are divided into three types; 46 data (45%) were identified as structural metaphors, 40 data (39%) were ontological metaphors, and 16 (16%) data were orientational metaphor. Based on the investigation of translation strategy, it was found that the translator applied the strategy of translating metaphor into metaphor by 72 data found (70.6%), metaphor into non-figurative language by 26 data found (25.5%), and metaphor into simile by 4 data found (3.9%).